THE DEVELOPMENT POLICY STRATEGY OF THE MANDALIKA TOURISM SPECIAL ECONOMIC ZONE, LOMBOK - Suryade, Lalu; Fauzi, Akhmad; Azam, Noer; Anggraini, Eva (Media Konservasi, 2022)
The development of the Mandalika Tourism Special Economic Zone (SEZ) is still running. Fluctuated economic and politic condition is in line with the changing national situation regarding policies of this SEZ. Being a new magnet of tourism, The Mandalika SEZ has demonstrated its role for coastal areas development in West Nusa Tenggara province. The sustainable development of this SEZ in the future are highly influenced by numerous action scenarios setting by stakeholders in multiple different layers. This research was aimed at analyzing a sustainable policy strategy for the Mandalika SEZ development in Central Lombok, Indonesia. It was conducted on October 2019 to March 2020. Data were gathered through in-depth interviews, Focus Group Discussions (FGD), and field observation. The MULTIPOL (a multicriteria-based policy analysis software) was used in seeking sundry possible implemented scenarios, policies, and actions. This research focused on establishing three scenarios, five policies, seven actions, and eleven evaluative criteria in analyzing the sustainability of the Mandalika Tourism SEZ. These numbers of scenarios, policies, actions, and criteria are established based on this research. The results of this research indicate the development of Mandalika Tourism SEZ currently can be conducted by integrating investment and local capacity empowerment (Blend-Based Scenario). The range values of this scenario starting from 12.2 (local-entrepreneurship policy) to 14.2 (man-made policy). This scenario accommodates policies both, developing local potency policies (local-entrepreneurship, and culture-tourism) and policies possibly opening investment (man-made, transportation-infrastructure, and adoption of information-communication-technology). The attention on balancing programs on either investment or empowering local capacity needs to be looked after by stakeholders in multi-level institutions. Key words: Policy, Strategy, MULTIPOL, Mandalika SEZ, Tourism